Persepsi Dampak Ujian dengan MCQ terhadap Proses Belajar Mahasiswa Fakultas Kedokteran - Irwin Aras; Gandes Retno Rahayu; Yayi Suryo Prabandari (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2014)
Background: Multiple choice question (MCQ) has been used widely as a method to assess the achievement of learning outcomes. MCQ as an assessment instrument may give both expected and unexpected impact. The research’s objective is to identify the impacts of MCQs in term of the structure, content, information and regulation on the learning process of student at Medical Faculty Hasanuddin University Method: The study was a descriptive survey involving 505 medical students from Hasanuddin University who were still in the academic phase, class of 2010, 2011 and 2012. Preliminary study was carried out to explore learning impacts caused by MCQs. Based on the result of preliminary study a questionnaire using rating scale was developed, consisting 92 items of possible learning impacts. Open ended questions were added to get free response from the students. The answers were classified into expected and unexpected learning impacts.Results: The structure, content, information and regulation of the MCQ method gave expected impacts such as learning from many sources (74.4%), group studying (96.2%), mind mapping (37.9%) and re-discussing the exam materials (96.2%). It also gave unexpected impacts such as guessing the answer (44.8%), only studying previous exams (93.5%), cheating (33.7%) and taking pictures of the exam papers (38.2%). Conclusion: Unexpected impacts may occur from the MCQ method, which structurally consists of item flaws, such as only assessing memorizing skills rather than the application of knowledge and incomplete information in the stem. The regulation, in the form of summative exam, will encourage students to prepare themselves more seriously if compared to the formative exam.